Effect of Smoking on the Red Blood Cell Count, Hemoglobin Concentration, Hematocrit and Red Cell Indices in Adult Male Smokers (Eastern Medical College Journal, 2022)
Background- Cigarette smoking is one of the common addictions. The effects of cigarette smoking on health are serious and, in many cases, deadly.Objectives: The present study was carried to observe the effect of smoking on Red Blood Cells (RBC) count, Hemoglobin (Hb) concentration, Hematocrit (HCT) and Red cell indices in adult male smokers and compare it with non-smokers to create awareness.Materials and Methods: In this study 50 adult male smokers and 50 adult male non-smokers aged from 20-45 years were taken. The smokers were regularly smoking for at least one year. Fresh peripheral blood sample from subjects were collected and analyzed for Red blood cell count, Hemoglobin concentration, Hematocrit and Red cell indices by using Mythmic-22 automated 5-part Hematology Analyzer.Result: In this study the values of RBCs count, Hb concentration and Hematocrit showed significant increase (p